Perang Jawa Terbesar (Perang Diponegoro) 1825-1830 dalam Pandangan Konsep Perang Semesta atau Total War - Agus Setyo Hartono (Ridwan Institute, 2021)
National hero, Javanese mystic, this war is the way or occurs in central Java with a variety of forces where the power, traditional power between dutch forces that have a modern style when cannons, long-barreled weapons, pistols use defense strategy Fort Stelsel.The purpose of this study to find out the war impulse impulse to or other areas of the base so the basis in the effort to release from the shackles. In contrast to the steps in other countries of the universe war which by Prince Diponegoroakan grace in the war concept that inspires war has the ability in his generation in addition to being able to live from a bold direction to act as a war Indonesia metamorphosed into a nation of strength that is growing in line with the military growth of other nations. The nation's economic economy is related to the role of persimmons in sub-district cities that are more strategic, the universe war becomes an alternative solution in the nation's problems. The research method by which riview literature exists is several research results on total war of war, issues, differences and differences from 9 qualitative and descriptive research studies. Results; 9 research of the people's village officials in the diponegro war has the name of the concept of war war and total war which is not sure the persimmon, populism and territory in the war that occurred. Discussions; In the Java war or Diponegoroan War, the concept of universal war is interesting to be studied about the universe war or total war there needs to be a proper involvement of community support in the container of the concept of universal war consisting of the universal, populist and regional unity concept of war in the future.